BREAST CANCER DETECTION WITH 99M TC MIBI IMAGING AND MAMMOGRAPHY - CHAIWATANARAT, Tawatchai; APINYANURAK, Chalermchai; BOONJUNWETWAT, Darunee; CHATAMRA, Kris; POSHYACHINDA, Makumkrong (The ASEAN Journal of Radiology, 2023)
Screening mammography in female patients provides good sensitivity in the detection of breast abnormalities but low specificity for the diagnosis of breast carcinoma. Thus many patients end up with unnecessary biopsy and/or lumpectomy. The use of nuclear medicine methods in detection of malignancy has been wildly studied with various radiopharmaceuticals. The objective of this study was to study the efficacy 99mTcMIBI scintimammography and mammography in the detection of breast carcinoma. The diagnosis would be made by pathological findings of the tissue or clinical follow up for at least 6 months. There were 33 female patients included in the study, among these there were 7 cases with known carcinoma of breast and clinically suspected of recurrent. Of all 33 cases, 14 cases was diagnosed as breast carcinoma and 19 cases as benign disease of the breasts. The results showed that sensitivity, specificity, accuracy, positive predictive value and negative predictive value of99mTc-MIBI scintimammography in the diagnosis of breast carcinoma were 93%, 100%, 97%, 100% and 95% respectively. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value of mammography were 100%, 63%, 79%, 67% and 100% respectively. We concluded that99mTc-MIBI scintimammography has a good efficacy and increase specificity of mammography in the diagnosis of breast carcinoma. We suggested that patients should have mammography performed first, if the lesion is indeterminated by mammography then99mTc-MIBI scintimammography will be the next step for investigation.